Card Sort Strategy to Improve Arabic Reading Skills at Al-Ikhlas Islamic Boarding School Taliwang - Subliansyah; Fauzan Rahman (IJAS: International Journal of Arabic Studies, 2025)
Research related to the implementation of the card sort strategy in improving reading proficiency is motivated by the low ability of students in reading Arabic texts in class 2 in Al-Ikhlas Taliwang Islamic Boarding School. 30 students only 10 students can read fluently, if presented only 32% of students above average in reading. Therefore, researchers provide an idea in the form of implementing the Card Sort strategy in learning, where this strategy makes the teacher a facilitator and prioritizes active students in teaching and learning activities. This research aims to find out how effective the use of the card sort strategy is in learning and find out the steps for its implementation. The research method uses quantitative research with a type of experimental research, namely by comparing the results of students' pretest and posttest scores. To measure this, the researcher used Paired Sample T Test analysis. The results of the research obtained an average student pretest score of 42.7 and for the posttest it was 63.7, this shows an increase in students' abilities. If you pay attention to the analysis test results using SPSS 25, the Sig value is obtained. (2-tailed) of 0.000 < 0.005, if you read it there is a significant difference between the students' pretest and posttest scores.